Forms of comprehension. Issue 3 (November 2020) - McCormack, Derek
This commentary addresses a series of questions that emerge from James Ash's paper. In doing so it foregrounds issues of temporality, flatness, entities, worlds, and politics. It uses a consideration of these issues to reflect briefly on the relations between ontologies and on the question of comprehension as a particular form of relation.